Crossed Swords : Pakistan, Its Army, And the Wars Within - Nawaz, Shuja (Karachi Oxford University Press, 2008)
"Based on 30 years of research and analysis, this definitive book is a profound, multi-layered, and historical analysis of the nature and role of the Pakistan Army in the country's polity as well as its turbulent relationship with the United States."--Jacket.
Includes Bibliography, Appendix and Index.
Keywords: Pakistan -- Pakistan. Army -- United States